Four‐Membered Heterometallacyclic d0 and d1 Complexes of Group 4 Metallocenes with Amidato Ligands. Issue 25 (23rd May 2014) - Haehnel, Martin; Priebe, Jacqueline B.; Yim, Jacky C.‐H.; Spannenberg, Anke; Brückner, Angelika; Schafer, Laurel L.; Rosenthal, Uwe
Abstract A study of the coordination chemistry of different amidato ligands [(R)NC(Ph)O] (R=Ph, 2, 6‐diisopropylphenyl (Dipp)) at Group 4 metallocenes is presented. The heterometallacyclic complexes [Cp2M(Cl)κ2‐N, O‐(R)NC(Ph)O] M=Zr, R=Dipp (1 a), Ph (1 b); M=Hf, R=Ph (2)) were synthesized by reaction of [Cp2MCl2] with the corresponding deprotonated amides. Complex 1 a was also prepared by direct deprotonation of the amide with Schwartz reagent [Cp2Zr(H)Cl]. Salt metathesis reaction of [Cp2Zr(H)Cl] with deprotonated amide [(Dipp)NC(Ph)O] gave the zirconocene hydrido complex [Cp2M(H)κ2‐N, O‐(Dipp)NC(Ph)O] (3). Reaction of 1 a with Mg did not result in the desired Zr(III) complex but in formation of Mg complex [(py)3Mg(Cl) κ2‐N, O‐(Dipp)NC(Ph)O] (4; py=pyridine). The paramagnetic complexes [Cp′2Tiκ2‐N, O‐(R)NC(Ph)O] (Cp′=Cp, R=Ph (7 a); Cp′=Cp, R=Dipp (7 b); Cp′=Cp*, R=Ph (8)) were prepared by the reaction of the known titanocene alkyne complexes [Cp2′Ti(η2‐Me3SiC2SiMe3)] (Cp′=Cp (5), Cp′=Cp* (6)) with the corresponding amides. Complexes 1 a, 2, 3, 4, 7 a, 7 b, and 8 were characterized by X‐ray crystallography. The structure and bonding of complexes 7 a and 8 were also characterized by EPR spectroscopy.